Educating the nation: shaping student-citizens in Indonesian schools. Issue 3 (3rd May 2016) - Moser, Sarah
Abstract : Children in Indonesia experience the state in ways that are vastly different from any other citizen. This article explores how the bodies of schoolchildren are a key site for nation-building practices in Indonesia through an examination of two state schools in Riau Islands Province. I investigate the ways in which national identity is inculcated in students through various performances intended to shape the student-citizen, including the wearing of school uniforms, morning national callisthenics and the weekly flag ceremony. Drawing on Judith Butler's concept of performativity, I argue that students' embodied performances of the nation can be understood as performative in the necessity of repetition or 'citational practices', which perpetuate the meaning and maintain the power associated. It is through repetition that meanings embedded in the performances of schoolchildren, such as hierarchy, awareness of a higher bureaucratic power and a sense of belonging to the nation, are perpetuated and normalized to the performers.